Assessment of shelf-life and metabolic viability of a multi-strain synbiotic using standard and innovative enumeration technologies - Visciglia, Annalisa; Allesina, Serena; Amoruso, Angela; De Prisco, Annachiara; Dhir, Raja; Bron, Peter A.; Pane, Marco (Frontiers in Microbiology, 2022)
The number of live bacterial cells is the most used parameter to assess the quality of finished probiotic products. Plate counting (PC) is the standard method in industry to enumerate cells. Application of PC implies critical aspects related to the selection of optimal nutrient media and growth conditions and underestimation of viable but not cultivable (VBNC) cells. Flow-cytometry (FC) is a culture-independent methodology having the potential to selectively enumerate live, damaged, and dead cells representing a powerful tool for in-depth monitoring of probiotic products. We monitored the shelf life of a clinical batch of a synbiotic composition PDS-08 targeting the pediatric population by means of PC and FC according to International Conference on Harmonization (ICH) pharma guidelines testing the Arrhenius model as predictive tool; PC enumeration revealed higher destruction rate than FC suggesting a faster reduction in cultivability than membrane integrity and thus a possible shift of the bacteria into a VBNC status. PDS-08 maintained acidification capability over time, when re-suspended in nutrient medium, even in samples tested sub-optimally for CFU detection (below 1 billion cells/dose). Due to similar kinetics described by the study of metabolic activity and membrane integrity, FC might be suggested as a valid tool for the study of functional stability of a probiotic product.